LINGUISTIC AND PSYCHOLINGUISTIC FOUNDATIONS FOR THE STUDY OF LEXICAL UNITS DENOTING HUMAN CHARACTER IN THE ENGLISH AND KARAKALPAK LANGUAGES - Urazbaeva, Dilbar Turdibaevna (SCIENCE and SOCIETY, 2026)
The article is devoted to a comprehensive theoretical and methodological analysis of units denoting human character in English and Karakalpak. The study examines interpretations of the concept of “character” in psychology, linguistics, and cognitive science, as well as the mechanisms of its linguistic representation.
Keywords: character; linguistic worldview; evaluative semantics; connotation; cognitive linguistics; contrastive analysis